Integrated farming systems for enhancing productivity and livelihood of small farmers - Kumar, Sunil; Singh, Raghuveer; Kumar, Kamlesh (Indian Farming, 2025)
Integrated Farming System (IFS) offers a viable solution by integrating multiple enterprises. The by-products of one enterprise serve as valuable inputs for another, thereby fostering resource recycling, labour use efficiency, and reduced market dependency. By promoting year-round productivity, IFS significantly improves livelihood security. IFS minimizes risks from crop failures, market fluctuations, and impacts of climatic variability. Thus, IFS is a resilient, and farmer-centric model, particularly suited to the needs of small and marginal farmers in India. Despite challenges of investment, management, and market linkages, the long-term economic, nutritional, and ecological benefits establish IFS as a cornerstone for sustainable agriculture in India.